Studi Deskriptif Tentang Profil Kepribadian Berdasarkan Cattel’s Sixteen Personality Factors (16 Pf) Pada Atlet Olahraga Cabang Menembak Jawa Barat - Hedi Wahyudi (Universitas Islam Bandung, 2011)
Background problems in this study are base on the phenomenon of West Java Performance athletes shoot low ands shooting sports sequences that fall into the category of main stay 2. The ability of athletes affected by psychological factors. One of which is personality. Coach argued that the shooting athlete lack adequate to deal with mental game. Athletes have not been able to demonstrate appropriate behavior with the behavior of the ideal athlete who demands the firing of certain personality characteristic. Picture of the ideal personality of shoot athletes have nearly the same explanation with some of explanation personality factors put forward by Bernard Raymond Cattel. Shooting sport require athletes who have control the thoughts, actions, and emotions, the ability of a high concentration, and confidence. The purpose of this study was to gain insight about the personality profile athletes shoot in West Java. The Study population was all athletes shoot West Java being included in the qualifying round of PON. Where populations totaling fifteen people measuring instrument used are test kits that measure personality, namely Cattel 16 PF of which consist of 105 questions. This study is a qualitative description study in analyzing the data so the research results are not used statistical test, Count statistics used only simple statistic calculation of the mean data. The data is then analyzed and interpreted. Based on the calculated mean of seven personality factors directly related to the shooting sports. It seems that in general score is dominated by athletes shoot the normal category and are moving toward low normal. This shows that athletes do not have a personality that matches the characteristics of the ideal athlete to shoot. When seeing the personality profile of each athlete, there are still some athletes who have a factor that does not fit more than a factor that matches the characteristics of the ideal athlete to shoot. In General. Factors that do not fit these are the factors C (emotional stability) is low, the factor L (vigilance) is high, and factors Q3 (perfectionism) is low.